Method for in-situ production of metal graphene composite material
By producing metal graphene composites in situ, the problems of poor consistency, uneven dispersion and low purity in the preparation of existing graphene alloys are solved, and the preparation of graphene composites with high purity and high content is achieved, reducing cost and operational complexity.
Patent Information
- Application Number
- CN202411962257.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing graphene alloys have problems such as high cost, poor alloy consistency, uneven graphene dispersion, low graphene content, low purity and complex preparation methods, and it is difficult to prepare graphene composite materials with specific content as needed.
The method of producing metal graphene composite materials in situ is adopted to ensure uniform dispersion and high purity of graphene by preparing a parent alloy with high graphene content and mixing it with metal or metal alloy in an induction furnace.
High purity (≥99%) and high graphene content (≥0.0014%) of graphene composite materials are achieved, and different contents of graphene composite materials can be prepared as needed, reducing production costs and operational complexity.
Smart Images

Figure CN119736512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene composite materials, and in particular to a method for in-situ production of metal graphene composite materials. Background Art
[0002] Graphene is one of the strongest materials known. It also has good toughness and can be bent. The theoretical Young's modulus of graphene is 1.0 TPa and the inherent tensile strength is 130 GPa. The carrier mobility of graphene at room temperature is about 15000 cm 2 / (V·s), which is more than 10 times that of silicon and more than twice that of indium antimonide (InSb), the material with the highest known carrier mobility. Under certain specific conditions, such as low temperature, the carrier mobility of graphene can even reach 250,000 cm 2 / (V·s). Unlike many materials, the electron mobility of graphene is less affected by temperature changes. At any temperature between 50 and 500K, the electron mobility of a single layer of graphene is 15000cm 2 / (V·s) approximately.
[0003] Due to the many excellent properties of graphene itself, it has been applied in more and more fields. In recent years, with the rapid development of new energy and energy storage fields, the application of graphene in the field of batteries has become more and more common. For example, it is directly added to active materials as a battery additive to improve the porosity of active materials, enhance the conductivity and charging acceptance of active materials, and improve the anti-sulfurization performance and deep cycle performance of batteries. Adding graphene to grid alloys to prepare graphene alloys can improve the conductivity and mechanical properties of the alloys, effectively solve the problem of active material and grid interface bonding, and avoid premature capacity loss. At the same time, it can greatly improve the corrosion resistance and creep resistance of the grid, effectively extending the service life of the battery. Because of the excellent properties of graphene alloys, graphene alloys have been widely used in the field of battery energy. The use of graphene in batteries has greatly improved the performance indicators of batteries, but the preparation of graphene alloys still has problems such as high cost, poor alloy consistency, uneven graphene dispersion, low graphene content, low purity, complex preparation methods, and inability to prepare specific content of graphene as needed. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide a method for in-situ production of metal graphene composites, so as to solve at least one of the problems that the existing methods cannot prepare composite materials with specific graphene content as required, the graphene content is uncontrollable, and the prepared composite materials have low purity, uneven dispersion, complex preparation method, high cost, etc.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for in-situ production of a metal graphene composite material, comprising: preparing a master alloy of the metal graphene composite material, melting the master alloy and a metal at 350-400° C., stirring evenly, and pouring the mixture into a second mold to obtain the metal graphene composite material;
[0007] Wherein, the mass relationship between the metal and the master alloy is as follows:
[0008]
[0009] Mpure: the mass of the metal, in g;
[0010] Cinitial: mass fraction of graphene in the master alloy;
[0011] Minitial: mass of master alloy, in g;
[0012] C Required: The mass fraction of graphene in the metal graphene composite material to be prepared.
[0013] Furthermore, the second mold is preheated at 250-300° C. for 1-2 hours.
[0014] Furthermore, the master alloy is prepared by the following method:
[0015] (1) melting KCl and ZnCl2 to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture;
[0016] (2) Add the mixture to a metal or metal alloy, load it into a silicon carbide crucible, place it in a heating and stirring device, heat it to melt, and let it stand to separate into layers, wherein the upper layer is the molten salt mixture and the lower layer is the master alloy.
[0017] Furthermore, in step (1), the molar ratio of KCl to ZnCl2 is 1:0.7 to 1.6, preferably, 1:0.7 to 1.5.
[0018] Furthermore, in step (1), the melting temperature is 750-850° C., and the melting and dehydration time is 20-50 min.
[0019] Furthermore, in step (1), the mass of boron carbide accounts for 2-5% of the total mass of KCl and ZnCl2, preferably, 3-5%.
[0020] Furthermore, in step (2), the mass of the metal or metal alloy is 1 to 1.6 times, preferably 1 to 1.5 times, the total mass of KCl and ZnCl2.
[0021] Furthermore, in step (2), the heating and melting temperature is 650-750° C. and the time is 1-3 hours.
[0022] Furthermore, the metal is at least one of lead, aluminum or zinc.
[0023] Furthermore, the method further comprises pouring the statically layered upper layer of the molten salt mixture into a container made of refractory ceramics or stainless steel, and pouring the remaining small amount of the molten salt mixture and the lower layer material into a first mold to obtain the master alloy.
[0024] Furthermore, the first mold needs to be preheated at a temperature of 250-300° C. for 1-2 hours.
[0025] In a second aspect, the present invention provides a metal graphene composite material prepared by the above method.
[0026] In a third aspect, the present invention provides an application of the above-mentioned metal graphene composite material in battery materials.
[0027] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0028] (1) The present invention first prepares a master alloy, the carbon content in the master alloy greatly exceeds the solubility limit, so that the carbon can be saturated in the metal melt to form a graphene structure, and then dilutes it by adding metal to obtain a metal-graphene composite material with a target content. The method of the present invention can prepare metal-graphene composite materials with different graphene contents as needed.
[0029] (2) In the preparation method of the master alloy of the present invention, KCl and ZnCl2 are first melted, which, on the one hand, fully dehydrates the salt, and on the other hand, reduces the melting point of the molten mixed salt, and the temperature required for the secondary melting is lower, which is conducive to the reaction and can increase the content of graphene. In the present invention, by adding molten salt pretreatment, it can be melted with the metal or metal alloy at a lower temperature, which is more conducive to the reaction, so that the graphene content in the product is further increased, and it is also conducive to reducing the size and number of graphene layers, and improving the purity of the composite material. The purity of the composite material of the present invention is ≥99%, and the graphene content is ≥0.0014%. Preferably, the graphene content is 0.023%;
[0030] (3) The metal master alloy described in the present invention is made in an induction furnace. In the induction furnace, due to the electric force, the convection of the metal melt is ensured and the mixing of the metal melt is achieved. Molten salt is not conductive, so it can only heat the molten metal and will not move under the action of electromagnetic force. The convection in the molten salt is essentially just heat flow. The salt heated by the metal rises from the molten metal-salt interface to the salt-furnace atmosphere interface and is replaced by the cooler salt, which ensures the continuous movement of the molten metal-salt interface. The method of the present invention has lower energy consumption, is more convenient to operate, and does not require additional mechanical stirring treatment.
[0031] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0033] Figure 1 This is a SEM image of the composite material prepared in Example 1 of the present invention;
[0034] Figure 2 This is a BES diagram of the composite material prepared in Example 1 of the present invention;
[0035] Figure 3 This is the Raman spectrum of the composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0037] A specific embodiment of the present invention discloses a method for in-situ production of a metal graphene composite material, comprising: preparing a master alloy of the metal graphene composite material, melting the master alloy and a metal at 350-400° C., stirring evenly, and pouring the mixture into a second mold to obtain the metal graphene composite material;
[0038] Wherein, the mass relationship between the metal and the master alloy is as follows:
[0039]
[0040] Mpure: the mass of the metal, in g;
[0041] Cinitial: mass fraction of graphene in the master alloy;
[0042] Minitial: mass of master alloy, in g;
[0043] C Required: The mass fraction of graphene in the metal graphene composite material to be prepared.
[0044] Compared with the prior art, the present invention uses graphene film for metal strengthening technology, that is, the carbon content in the melt greatly exceeds the solubility limit, and then releases the graphene structure (enhancing the mechanical properties of the lead-graphene composite) during the crystallization (from liquid to solid); the present invention first prepares a master alloy, the carbon content in the master alloy greatly exceeds the solubility limit, and the carbon can be saturated in the metal melt to form a graphene structure, and then dilutes it by adding metal to obtain a metal-graphene composite material with a target content. The method of the present invention can prepare metal-graphene composite materials with different graphene contents as needed.
[0045] The present invention prepares the metal graphene composite material in the form of a master alloy. First, a master alloy with a high graphene content is prepared. The master alloy can be mixed with a metal or a conventional metal alloy in a certain proportion before use. Since the production of graphene composite materials requires special materials and equipment, the present invention can realize the production of the master alloy by the production party and transport it to the user for dilution before use, thereby reducing the production cost and transportation cost.
[0046] In a specific embodiment, the second mold is preheated at 250-300°C (e.g., 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C) for 1-2h (e.g., 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h).
[0047] If the mold temperature is too low, the lead will cool too quickly, resulting in large shrinkage cavities and affecting subsequent use; if the mold temperature is too high, the lead will cool too slowly, causing component segregation.
[0048] In a specific embodiment, the master alloy is prepared by the following method:
[0049] (1) melting KCl and ZnCl2 to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture;
[0050] (2) Add the mixture to a metal or metal alloy, load it into a silicon carbide crucible, place it in a heating and stirring device, heat it to melt, and let it stand to separate into layers, wherein the upper layer is the molten salt mixture and the lower layer is the master alloy.
[0051] In the preparation method of the master alloy of the present invention, KCl and ZnCl2 are first melted, so that the salt is fully dehydrated on the one hand, and the melting point of the mixed salt after melting is reduced on the other hand, and the temperature required for secondary melting is lower, which is conducive to the reaction and can increase the content of graphene. In the present invention, by adding molten salt pretreatment, it can be melted with metal or metal alloy at a lower temperature, which is more conducive to the reaction, so that the content of graphene in the product is further increased, and it is also conducive to reducing the size and number of graphene layers and improving the purity of the composite material.
[0052] The carbon source in the method of the present invention comes from boron carbide. Boron carbide decomposes under specific conditions to form carbon atoms, which enter into the lead liquid and reorganize to form a graphene structure after reaching a certain concentration. Therefore, the combination of graphene and lead in the master alloy prepared by the method of the present invention is better and the dispersion is more uniform. Secondly, graphene is expensive. Compared with the method of directly adding graphene, the method of the present invention has a cost advantage.
[0053] Preferably, the heating and stirring device described in the present invention is an induction furnace. The carbon content in the master alloy prepared by the method of the present invention greatly exceeds the solubility limit. The preparation method is simple, the preparation time is short, the production cost is low, and no mechanical stirring is used. The induction furnace is used for reaction, which can reduce impurities introduced by stirring, and the stirring step can be omitted to simplify the operation. In addition, the induction furnace heats up quickly, which can shorten the heating and melting time.
[0054] In a specific embodiment, in step (1), the molar ratio of KCl to ZnCl2 is 1:0.7-1.6, preferably, 1:0.7-1.5, for example, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5.
[0055] The melting point of a mixed salt of KCl and ZnCl2 is lower than that of a single salt. Within the above molar ratio range, the melting point is relatively low near the eutectic point of KCl and ZnCl2.
[0056] Experiments show that the separation of carbon from salt into lead is related to the type of salt and temperature, and the salt and temperature selected by the present invention are more conducive to this process. In order to ensure that carbon provides more effective exchange at the phase boundary between the metal and the salt slag carrier, the salt slag uses KCl and ZnCl2.
[0057] In a specific embodiment, in step (1), the melting temperature is 750-850°C, for example, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, and the melting dehydration time is 20-50 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min.
[0058] Within the above melting temperature and time, KCl and ZnCl2 can be fully melted with low energy consumption and will not affect the service life of the equipment.
[0059] In a specific embodiment, in step (1), the crushed particle size is less than 3 mm, which is conducive to uniform mixing with boron carbide.
[0060] In a specific embodiment, in step (1), the mass of boron carbide accounts for 2-5% of the total mass of KCl and ZnCl2, preferably, 3-5%, for example, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5%. Since boron carbide is a carbon source, it must be excessive to ensure sufficient graphene content in the product.
[0061] In a specific embodiment, in step (2), the mass of the metal or metal alloy is 1 to 1.6 times the total mass of KCl and ZnCl2, preferably, 1 to 1.5 times, for example, 1 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times.
[0062] In a specific embodiment, in step (2), the heating and melting temperature is 650-750°C, for example, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, and the time is 1-3h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h, 2.8h, 3h.
[0063] Lower temperature is not conducive to the reaction, higher temperature will increase the loss of salt volatilization and energy consumption, so the above temperature range is selected. The time is related to the graphene content, the longer the time, the higher the content.
[0064] The metal master alloy described in the present invention is made in an induction furnace. In the induction furnace, due to the electric force, the convection of the metal melt is ensured and the mixing of the metal melt is achieved. Molten salt does not have electrical conductivity, so it can only heat the molten metal and will not move under the action of electromagnetic force. The convection in the molten salt is essentially just a heat flow. The salt heated by the metal rises from the molten metal-salt interface to the salt-furnace atmosphere interface and is replaced by the colder salt, which ensures the continuous movement of the molten metal-salt interface. This is because boron carbide and salt are mixed together, and the salt at the metal-salt interface moves upward under the action of the heat flow, and the colder salt at the top sinks, and the boron carbide also accompanies the same movement. The material at the metal-salt interface is constantly changing, thereby playing a stirring role, and no additional mechanical stirring is required.
[0065] In a specific embodiment, the method further comprises pouring the statically layered upper layer of the molten salt mixture into a container made of refractory ceramics or stainless steel, and pouring the remaining small amount of the molten salt mixture and the lower layer material into a first mold to obtain the master alloy.
[0066] Specifically, the first mold needs to be preheated at a temperature of 250-300°C (for example, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C) for 1-2h (for example, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h).
[0067] If the mold temperature is too low, the lead will cool too quickly, resulting in large shrinkage cavities and affecting subsequent use; if the mold temperature is too high, the lead will cool too slowly, causing component segregation.
[0068] It should be noted that the first mold is preheated in a low-temperature resistance furnace, and the low-density molten salt floats in the form of slag, and can be easily separated from the ingot after being taken out of the mold. The separated molten salt can be used in step (1).
[0069] In the present invention, the purity of pure lead is 99.99%, the purity of KCl is 99.8%, the purity of ZnCl2 is 99.8%, the purity of boron carbide is ≥96.0%, and the particle size of boron carbide is at least F220.
[0070] In a specific embodiment, the graphene content in the master alloy is 0.015-0.025%, and the hardness is 4.8-5.0 HB.
[0071] Preferably, the graphene content in the master alloy is 0.023-0.025%, and the hardness is 4.9-5.0 HB.
[0072] In a specific embodiment, the carbon in the master alloy is modified into graphene.
[0073] In a specific embodiment, the metal is at least one of lead, aluminum or zinc.
[0074] The purity of the master alloy prepared by the method of the invention is ≥99.93%, and the purity of the metal graphene composite material is ≥99.96%.
[0075] Another specific embodiment of the present invention discloses a metal graphene composite material prepared by the above method.
[0076] Preferably, the metal graphene composite material prepared by the present invention has at least 2 graphene layers, preferably 2 layers, a purity of ≥99.6%, a graphene content of 0.0014-0.023%, preferably a graphene content of 0.023%, and a hardness of 4.6-4.7HB.
[0077] Another specific embodiment of the present invention discloses an application of the above-mentioned metal graphene composite material in battery materials.
[0078] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0079] In the following examples of the present invention, the purity of pure lead is 99.99%, the purity of KCl is 99.8%, the purity of ZnCl2 is 99.8%, the purity of boron carbide is 96.0%, and the particle size of boron carbide is F220.
[0080] Example 1
[0081] A method for in-situ production of a metal-graphene composite material comprises the following steps:
[0082] (1) KCl and ZnCl2 were mixed in a molar ratio of 1:1 (total mass of 450 g), placed in a silicon carbide crucible in a Graficarbo resistance furnace, melted and dehydrated at 750° C. for 40 min, cooled, crushed to a particle size of less than 3 mm, and 15 g of boron carbide was added to obtain a mixture;
[0083] (2) 600 g of pure lead was mixed with the mixture, loaded into a silicon carbide crucible, placed in a YiHui M.MF.00004 induction furnace, heated and melted at a temperature of 700° C. for 2 h to obtain an upper and lower layer of material, the upper layer being a molten salt mixture, and the lower layer being a master alloy, the molten salt mixture was poured into a container made of refractory ceramics or stainless steel, and the remaining small amount of molten salt mixture and the master alloy were poured into a first metal mold together, wherein the first metal mold was preheated to 300° C. for 1 h in a low-temperature resistance furnace SNOL 58 / 350, and the low-density molten salt floated in a slag state, and was easily separated from the master alloy ingot after being taken out of the first mold, wherein, after checking the carbon modification on a Renishaw INVIA0820-04 confocal Raman scattering spectrometer, the carbon content in the master alloy was 0.025%, and the carbon modification was graphene;
[0084] (3) In order to obtain a metal-graphene composite material with a graphene mass fraction of 0.0023%, 50 g of the master alloy and 493 g of pure lead were melted at 370°C, the melt was kept at a given temperature for 15 min, and then manually mixed with a stainless steel stirrer, and the surface slag was removed with a stainless steel skimmer until the metal was mirror-like; and poured into a second metal mold preheated at 290°C for 1 h to obtain a metal-graphene composite material.
[0085] Example 2
[0086] A method for in-situ production of a metal-graphene composite material comprises the following steps:
[0087] (1) KCl and ZnCl2 are mixed in a molar ratio of 1:0.7, placed in a silicon carbide crucible in a Graficarbo resistance furnace, melted and dehydrated at 850° C. for 50 min, cooled, and crushed to a particle size of less than 3 mm, and boron carbide is added, wherein the mass of boron carbide accounts for 4% of the total mass of KCl and ZnCl2, to obtain a mixture;
[0088] (2) Mixing pure lead with the mixture, wherein the mass of the pure lead is 1 times the total mass of KCl and ZnCl2, and loading the mixture into a silicon carbide crucible, placing the mixture in a YiHui M.MF.00004 induction furnace, and heating and melting the mixture at 750°C for 1 hour to obtain two layers of material, the upper layer being a molten salt mixture, and the lower layer being a master alloy. The molten salt mixture is poured into a container made of refractory ceramics or stainless steel, and the remaining small amount of the molten salt mixture and the master alloy are poured into a first metal mold together, wherein the first metal mold is preheated to 300°C for 1 hour in a low-temperature resistance furnace SNOL 58 / 350, and the low-density molten salt floats in a slag state, and is easily separated from the master alloy ingot after being taken out of the first mold. wherein, after checking the carbon modification on a Renishaw INVIA0820-04 confocal Raman scattering spectrometer, the carbon content in the master alloy is 0.024%, and the carbon modification is graphene;
[0089] (3) In order to obtain a metal-graphene composite material with a graphene mass fraction of 0.0023%, 50 g of the master alloy and 472 g of pure lead were melted at 400°C, the melt was kept at a given temperature for 15 min, and then manually mixed with a stainless steel stirrer, and the surface slag was removed with a stainless steel skimmer until the metal was mirror-like; and poured into a second metal mold preheated at 250°C for 2 h to obtain a metal-graphene composite material.
[0090] Example 3
[0091] A method for in-situ production of a metal-graphene composite material comprises the following steps:
[0092] (1) KCl and ZnCl2 are mixed in a molar ratio of 1:1.5, placed in a silicon carbide crucible in a Graficarbo resistance furnace, melted and dehydrated at 800° C. for 50 min, cooled, crushed to a particle size of less than 3 mm, and added with boron carbide, wherein the mass of the boron carbide accounts for 5% of the total mass of KCl and ZnCl2, to obtain a mixture;
[0093] (2) mixing lead with the mixture, wherein the mass of pure lead is 1.5 times the total mass of KCl and ZnCl2, and loading the mixture into a silicon carbide crucible, placing the mixture in a YiHui M.MF.00004 induction furnace, and heating and melting the mixture at a temperature of 650°C for 3 hours to obtain an upper and lower layer of material, wherein the upper layer is a molten salt mixture and the lower layer is a master alloy. The molten salt mixture is poured into a container made of refractory ceramics or stainless steel, and the remaining small amount of the molten salt mixture and the master alloy are poured into a first metal mold together, wherein the first metal mold is preheated to 275°C for 1.5 hours in a low-temperature resistance furnace SNOL 58 / 350, and the low-density molten salt floats in a slag state, and is easily separated from the master alloy ingot after being taken out of the first mold. wherein, after checking the carbon modification on a Renishaw INVIA0820-04 confocal Raman scattering spectrometer, the carbon content in the master alloy is 0.023%, and the carbon modification is graphene;
[0094] (3) In order to obtain a metal-graphene composite material with a graphene mass fraction of 0.0023%, 50 g of the master alloy and 450 g of pure lead were melted at 350°C, the melt was kept at a given temperature for 15 min, and then manually mixed with a stainless steel stirrer, and the surface slag was removed with a stainless steel skimmer until the metal was mirror-like; and poured into a second metal mold preheated at 300°C for 1.5 h to obtain a metal-graphene composite material.
[0095] Example 4
[0096] The method for preparing a metal graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (1), the molar ratio of KCl to ZnCl2 is 1:1.6.
[0097] Example 5
[0098] The method for preparing a metal graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (1), the mass of boron carbide accounts for 2% of the total mass of KCl and ZnCl2.
[0099] Example 6
[0100] The method for preparing a metal graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (2), the mass of lead is 1.6 times the total mass of KCl and ZnCl2.
[0101] Comparative Example 1
[0102] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (1), KCl, ZnCl2 and boron carbide are directly mixed without melting, cooling and pulverizing KCl and ZnCl2.
[0103] Comparative Example 2
[0104] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (2), the heating and melting temperature is 760° C. and the time is 2.2 h.
[0105] Comparative Example 3
[0106] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (2), an open furnace is used for melting in a mechanical stirrer instead of an induction furnace for heating.
[0107] Comparative Example 4
[0108] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (3), the melting temperature is 410°C.
[0109] Comparative Example 5
[0110] The preparation method of a metal-graphene composite material in this comparative example is the same as that in Example 1, except that ZnCl2 is replaced by NaCl.
[0111] Test Example 1
[0112] The purity, graphene content and number of layers of the master alloys and metal graphene composite materials prepared in Examples 1-6 and Comparative Examples 1-5 were tested respectively. The hardness of the composite materials was tested by a VERZUS 750CCD hardness tester. The results are shown in Table 1.
[0113] Among them, the graphene layer number detection method:
[0114] In the present invention, the number of graphene layers is characterized by Raman spectroscopy, and the number of graphene layers is calculated based on the intensity relationship between the 2D peak and the G peak. The test is performed using a Renishaw INVIA0820-04 confocal Raman scattering spectrometer.
[0115] Figure 3 The Raman spectrum test results of Example 1 are shown. The Raman spectrum shows that the test sample is a typical multilayer graphene structure. According to the intensity ratio of the 2D and G peaks, I2D / IG is equal to 0.60, indicating that the material at this test point forms two layers of graphene. The G peak is significantly higher than the D peak, indicating that the number of graphene defects is small. The products obtained in other embodiments or comparative examples are also tested using the same method.
[0116] Table 1
[0117]
[0118] Compared with Example 1, Comparative Example 1 does not adopt the raw material pretreatment process designed by the present invention. The graphene content in the prepared master alloy is significantly reduced, the purity and hardness of the composite material are also slightly reduced, and the number of graphene layers is increased to 3 layers.
[0119] Compared with Example 1, the graphene content in the prepared master alloys of Examples 4-6 is reduced, the purity of the composite material in Example 4 is also reduced, and the number of graphene layers is increased to 3 layers.
[0120] Comparative Example 2 Compared with Example 1, the graphene content in the master alloy prepared at a temperature other than that of the present invention is significantly reduced, the purity and hardness of the composite material are also slightly reduced, and the number of graphene layers is increased to 3 layers.
[0121] Comparative Example 3 Compared with Example 1, the graphene content in the master alloy prepared by the induction furnace heating melt method designed by the present invention is basically the same, but the ordinary furnace heats up slowly, and mechanical stirring makes the production process more complicated. In addition, some impurities are introduced due to mechanical stirring, resulting in reduced purity of the composite material.
[0122] Comparative Example 4 Compared with Example 1, the graphene content in the metal-graphene composite material not prepared at the temperature of the present invention is significantly reduced.
[0123] Compared with Example 1, Comparative Example 5 does not use the raw materials designed by the present invention, and the graphene content in the prepared master alloy is significantly reduced.
[0124] Test Example 2
[0125] The graphene composite material obtained in Example 1 was sampled at different positions to test the carbon content. The obtained data are shown in Table 2. The microscopic morphology of the cross section of the composite material was observed, and its SEM and BES images are shown in Table 2. Figure 1 and 2 shown.
[0126] Table 2 Test data of carbon content at different positions of graphene composite materials
[0127] Position number Carbon content (%) 1 0.0024 2 0.0025 3 0.0026 4 0.0025 5 0.0025 6 0.0027 7 0.0023 8 0.0025
[0128] It can be seen from the above table that the carbon content in the graphene composite materials at different positions is not much different, indicating that the composite materials prepared by the method of the present invention have good consistency.
[0129] from Figure 1 and 2 It can be seen that in the graphene composite material prepared by the method of the present invention, the graphene film is small in size and evenly dispersed, without agglomeration or agglomeration.
[0130] The inventors conducted the above test on the composite materials prepared in other embodiments, and the results were basically the same. Due to limited space, they are not listed one by one.
[0131] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for in-situ production of metal graphene composite materials, characterized in that: include: Preparing a master alloy of a metal-graphene composite material, melting the master alloy and a metal at 350-400° C., stirring evenly, and pouring the mixture into a second mold to obtain the metal-graphene composite material; Wherein, the mass relationship between the metal and the master alloy is as follows: Mpure: the mass of the metal, in g; Cinitial: mass fraction of graphene in the master alloy; Minitial: mass of master alloy, in g; C Required: The mass fraction of graphene in the metal graphene composite material to be prepared.
2. The method for in-situ production of metal graphene composite materials according to claim 1, characterized in that: The second mold is preheated at 250-300° C. for 1-2 hours.
3. A method for in-situ production of metal graphene composite materials according to claim 1 or 2, characterized in that: The master alloy is prepared by the following method: (1) melting KCl and ZnCl2 to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture; (2) Add the mixture to metal or metal alloy, place it in a heating and stirring device, heat to melt, and allow to stand to separate into layers, wherein the upper layer is the molten salt mixture and the lower layer is the master alloy.
4. The method for in-situ production of metal graphene composite materials according to claim 3, characterized in that: In step (1), the molar ratio of KCl to ZnCl2 is 1:0.7-1.
6.
5. The method for in-situ production of metal graphene composite materials according to claim 3, characterized in that: In step (1), the melting temperature is 750-850° C., and the melting and dehydration time is 20-50 min.
6. The method for in-situ production of metal graphene composite materials according to claim 1, characterized in that: In step (1), the mass of boron carbide accounts for 2-5% of the total mass of KCl and ZnCl2.
7. The method for in-situ production of metal graphene composite materials according to claim 3, characterized in that: In step (2), the mass of the metal or metal alloy is 1 to 1.6 times the total mass of KCl and ZnCl2; The heating and melting temperature is 650-750°C and the time is 1-3 hours.
8. A method for in-situ production of a metal graphene composite material according to any one of claims 1 to 7, characterized in that: The metal is at least one of lead, aluminum or zinc.
9. A metal-graphene composite material prepared by the method according to any one of claims 1 to 8.
10. Use of the metal graphene composite material according to claim 9 in battery materials.
Citation Information
Patent Citations
Power cable fixing head
CN105755326A
Graphene reinforced magnesium-based composite material and preparation method thereof
CN113278840A
Positive grid alloy containing graphene and preparation method and application thereof
CN113579210A
Special corundum castable for circulating fluidized bed boiler and preparation method thereof
CN118561611A
Method of producing a composite material
GB201615658D0